Strategi Manajemen Risiko Sumber Daya Manusia dalam Meningkatkan Kinerja Organisasi - Jannah, Megia Zaharatul (CV. ITTC INDONESIA, 2025)
This study aims to analyze human resource (HR) risk management strategies in improving organizational performance. The approach used is a literature study with descriptive qualitative methods to examine various scientific sources related to the implementation of HR risk management in industrial organizations. The results of the study indicate that HR risk management plays a strategic role in maintaining organizational stability and increasing work effectiveness through four main stages: identification, analysis, mitigation, and monitoring of risks. Various industrial organizations implement strategies such as competency-based training, occupational safety and health (OHS), and reward systems for high-performing employees. These efforts have proven effective in reducing risks originating from human factors and increasing employee productivity and loyalty. However, in the digital era, organizations face the challenge of developing data-driven risk management systems and strengthening employee digital literacy. Thus, HR risk management plays a role not only as a control tool but also as an HR development strategy to achieve competitive advantage and organizational sustainability.